Yogurt natural y su efecto antidiarreico para cerdos en la etapa de recría en el litoral Ecuatoriano - Andrade Arroyo, Gema Alexandra (2018)
It is true that the post-weaning stage is critical in piglets, it leads to presentation of diarrhea; the use of yogurt in animal feed, allows to counteract stress produced by dietary changes; in this context, the effect of natural yogurt as an antidiarrheal was evaluated in York and Landrace breed pigs at 30-day-old rearing stage three treatments were used, corresponding T1 and T2 is supplied twice daily orally yogurt to concentration 1000.000 units Lactobacillus bulgaricus and Streptococcus thermophilus in volume five and ten ml respectively T0 (control) was not provided. They used seven pigs per treatment. Microbiological behavior was analyzed in which no significant differences were found, but in the results of laboratory analysis the T0 reported the presence of salmonella; T1 presented E.coli load at 1X104 CFU /; T2 reported nonexistences of these bacteria. The Completely Randomized Design (DCA) was used to analyze the productive parameters and there was no significant difference. The T0 obtained greater weight (102.87kg) and the smaller one is the T1 with 98.62kg; it is important to recall that the T2 is profiled until the fourth week with 22.38kg of weight and the conversion of 1.48kg; it is assumed that not feeding the Livitum causes stress due to unsatisfied appetite, which leads to deterioration in productive parameters. The feed conversion at the end of the preceding was higher in the T0 (1.21kg); the highest profitability was reported by T0 with 0.35 ctvs per dollar invested.